2014
DOI: 10.1021/om500528p
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Half-Sandwich Iron(II) and Iron(III) Complexes with N-Heterocyclic Carbene Ligands

Abstract: The cationic piano-stool iron complexes containing the N-heterocyclic carbene ligand tethered to a tetramethylcyclopentadienyl ring [(Cp*-NHC)Fe(CO)(L)]-[X] (L = NCMe, DMSO; X = BF 4 , OTf) have been prepared and analyzed by spectroscopic, electrochemical, and crystallographic methods. Oxidation reactions of the cationic complex [(Cp*-NHC)Fe(CO)(NCMe)][BF 4 ] (2) with silver tetrafluoroborate and tert-butyl hydroperoxide in acetonitrile yield the dicationic iron(III) complexes [(Cp*-NHC)Fe(NCMe) 2 ][BF 4 ] 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…The redox potentials can be estimated as the difference between the energies of the initial complex (1 or 2) and its oxidation product (1 + and 2 + ), in their optimised geometries, both in gas phase and in dichloromethane, as reported in previous studies of cyclopentadienyl complexes. 17 The calculated values (V relative to SCE) were calculated as 1.47 in gasphase and 0.68 (dichloromethane) for 1, and 1.53 in gasphase and 0.36 (dichloromethane) for 2, reproducing the trends observed in the experimental ones, although with a shi of $0.5 V.…”
Section: Syntheses Of Complexessupporting
confidence: 65%
See 1 more Smart Citation
“…The redox potentials can be estimated as the difference between the energies of the initial complex (1 or 2) and its oxidation product (1 + and 2 + ), in their optimised geometries, both in gas phase and in dichloromethane, as reported in previous studies of cyclopentadienyl complexes. 17 The calculated values (V relative to SCE) were calculated as 1.47 in gasphase and 0.68 (dichloromethane) for 1, and 1.53 in gasphase and 0.36 (dichloromethane) for 2, reproducing the trends observed in the experimental ones, although with a shi of $0.5 V.…”
Section: Syntheses Of Complexessupporting
confidence: 65%
“…58 The molecular structure and 3-d orbital representations were obtained with Molekel. 59,60 Redox potentials were estimated via DFT calculations, 17 according to the equation: E ¼ [(G Ox,solv. À G Red,solv. )…”
Section: Methodsmentioning
confidence: 99%
“…1 They are also known to be extremely unstable and most organometallics follow the 18-electron rule. Some stable coordinatively unsaturated 16-electron (16-e) complexes have been isolated in particular by the groups of Koelle, Tilley, Suzuki, among others, [2][3][4][5][6][7][8][9][10][11][12] but little is known about the reactivity of air and moisture stable 16-e complexes and about their properties in solution. Half-sandwich metal complexes are a particular class of organometallics which has attracted an enormous attention for the design of catalysts, 13 anticancer drug candidates, [14][15][16][17][18][19][20][21][22]23,24 and as building blocks for supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treatment of 5 with stoichiometric amounts of AgBF 4 yielded the corresponding cationic complex [(Cp‐NHC)Fe(CO)][BF 4 ], which was active in the reduction of ketones and sulfoxides, affording full conversions at 100 °C (Scheme ). These results demonstrated that smooth changes in the coordination sphere of iron have interesting implications on the catalytic activity of the metal complexes.…”
Section: Hydrosilylationmentioning
confidence: 99%